2009
DOI: 10.1016/j.jadohealth.2009.03.021
|View full text |Cite
|
Sign up to set email alerts
|

School Bullying Among Adolescents in the United States: Physical, Verbal, Relational, and Cyber

Abstract: Purpose Four forms of school bullying behaviors among US adolescents and their association with socio-demographic characteristics, parental support and friends were examined. Methods Data were obtained from the Health Behavior in School-Aged Children (HBSC) 2005 Survey, a nationally-representative sample of grades 6 to 10 (N = 7182). The Olweus Bully/Victim Questionnaire was used to measure physical, verbal and relational forms of bullying. Two items were added using the same format to measure cyber bullying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

112
1,122
22
104

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,604 publications
(1,360 citation statements)
references
References 21 publications
112
1,122
22
104
Order By: Relevance
“…Likewise, steep declines in emotional well-being arguably may lead to subsequent cyber-victimization. Youth take aim at those individuals who show signs of poor adjustment (Storch et al, 2007;Wang, Iannotti, & Nansel, 2009), and adolescents who are on a downward trajectory of lowered self-esteem or increased depressed mood may be the most vulnerable. Alternatively, early manifestation of any of these risks may be linked to later cyber-aggression, regardless of developmental change.…”
Section: Developmental Course Of Risk Indicatorsmentioning
confidence: 99%
“…Likewise, steep declines in emotional well-being arguably may lead to subsequent cyber-victimization. Youth take aim at those individuals who show signs of poor adjustment (Storch et al, 2007;Wang, Iannotti, & Nansel, 2009), and adolescents who are on a downward trajectory of lowered self-esteem or increased depressed mood may be the most vulnerable. Alternatively, early manifestation of any of these risks may be linked to later cyber-aggression, regardless of developmental change.…”
Section: Developmental Course Of Risk Indicatorsmentioning
confidence: 99%
“…In particular, previous research suggests that parents being available and open to communicate with children are in a better position to help avoid bullying and protect children from its negative consequences. In the United States of America (USA), the research conducted by Wang et al (2009) reported that parental behaviors involving positive communication to understand adolescents' concerns and problems, or skills to make upset adolescents feel better, actually protect them from bullying. Elgar et al (2014), also in the USA, reported that family communication and contact can help adolescents to be protected from the harmful effects of bullying.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Kapçı (2004), 40% of the responding adolescents reported being victim or bullyvictim of some forms of aggression. Wang et al (2009) found that 12.8% of young adolescents had been victimized from physical aggression and 13.3% had themselves perpetrated physical aggression. In a Turkish study, the prevalence of victimization from the following forms of physical aggression among young adolescents were: pushing 63.7%, damaging clothes or materials 45.2%, pinching 38.5%, kicking 27.2%, biting 22.8% and punching 16.4% (Yurtal & Cenkseven, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Kapçı (2004) found that 54% of the young adolescents reported being pushed, while 23% were slapped or kicked at least sometimes. Wang et al (2009) found that 36.5% of their respondents were victimized from verbal aggression, and 37.4% reported perpetration of verbal aggression; the most common form of verbal aggression being name-calling. Swearing, making fun of, name-calling and insulting are common forms of verbal aggression also in Turkey (Yurtal & Cenkseven, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation